#1.
1) b³-8c³=(b-2c)(x²+2bc+4c²)
2) 49x²y-y³=y(49x²-y²)=y(7x-y)(7x+y)
3) 7a²+14a+7=7(x²+2x+1)=7(x+1)²
4) 5ab-15b-5a+15=5(ab-3b-a+3)=5(b(a-3)-(a-3))=5(a-3)(b-1)
5) -1=(a²-1)(a²+1)=(a-1)(a+1)(a²+1)
#3.
1) a+b+a²-b²=a+b+(a-b)(a+b)=(a+b)(1+a-b)
2) 9a²-6ab+b²-16=(3a-b)²-16=(3a-b-4)(3a-b+4)
3) x³y²-x³-xy²+x=x(x²y²-x²-y²+1)=x(x²y²-x²-(y²-1))=x(x²(y²-1)-(y-1)(y+1))=x((x²(y-1)(y+1)-(y-1)(y+2))=x(y-1)(y+1)(x-1)(x+1)
4) 1-x²+4xy-4y²=1-(x²-4xy+4y²)=1-(x-2y)²=(1-x+2y)(1+x-2y)
#4.
1) 2x³-50x=0
x(2x²-50)=0
x=0 или 2x²-50=0
2x²=50
x²=25
x=5 или x=-5
Отв.: 5; -5; 0
2) 16x³+8x²+x=0
x(16x²+8x+1)=0
x=0 или 16x²+8x+1=0
D=64-4*16=0
x=(-8)/32=-0,25
x(4x+1)²=0
Отв: 0; -0,25
3) x³+2x²-36x-72=0
x²(x+2)-36(x+2)=0
(x+2)(x²-36)=0
(x+2)(x-6)(x+6)=0
x=-2;-6;6
Отв.: -2;-6;6